THE DEVELOPMENT OF SOCIAL AND MORAL RESPONSIBILITY IN TERMS OF RESPECT FOR THE RIGHTS OF OTHERS - Katie J Hughes; Laura Batten (Jurnal Ilmiah Peuradeun, 2016)
Social responsibility suggests that an individual has responsibility to the community or society in terms of choices about behaviors. Moral responsibility implies a knowledge and understanding of ‘right’ and ‘wrong’ and the ability and willingness to behave morally. These debates reflect the uncertainties about how moral and social responsibility can be conceptualized and promoted within modern societies. Adrift from moral certainties and wary of merely promoting dominant cultural norms, the role of moral reasoning and the ability to rationally choose between moral values is fore fronted, but leaves us with a concern that such choices may lack a coherent value base or ‘morality’. The debate leaves us with the question as to how we promote moral and social responsibility in young people as part of their learning in higher education in ways that promote moral reasoning but also develop values and ethical stances that go beyond, and can contest, the social norms of the times.